2023
DOI: 10.1002/chem.202301283
|View full text |Cite
|
Sign up to set email alerts
|

Tf2O‐Catalyzed Tandem Cyclization/Trifluoromethylselenolation of Alkynes for Synthesis of CF3Se‐Containing Heterocycles

Abstract: Herein, the tandem synthesis of various CF 3 Secontaining heterocyclic compounds has been developed, using Tf 2 O as the catalyst and trifluoromethyl selenoxides as the electrophilic trifluoromethylselenolation reagents. This process is characterized by its mild conditions, ease of operation, and good functional group compatibility. A variety of alkynes could be transferred into CF 3 Se-containing indoles, benzofurans, benzothiophenes, isoquinolines and chromenes in good yields. A key step involving the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Inspired by previously reported studies 27–31 and the potential use of 2-trifluoromethylseleno ethynylanilines ( 1 ) for the synthesis of trifluoromethylselenolated indoles, we wondered whether this class of reagents could bring about a SeCF 3 group migration, allowing alternative substitution patterns of indole products (Scheme 1d). Herein we report a practical zinc-mediated protocol for the synthesis of 2-substituted 3-trifluoromethylselenoindoles via a SeCF 3 migration.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by previously reported studies 27–31 and the potential use of 2-trifluoromethylseleno ethynylanilines ( 1 ) for the synthesis of trifluoromethylselenolated indoles, we wondered whether this class of reagents could bring about a SeCF 3 group migration, allowing alternative substitution patterns of indole products (Scheme 1d). Herein we report a practical zinc-mediated protocol for the synthesis of 2-substituted 3-trifluoromethylselenoindoles via a SeCF 3 migration.…”
Section: Introductionmentioning
confidence: 99%
“…When we were performing the tandem cyclization/trifluoromethylselenolation of alkynes, we observed that a ketone could be obtained as one of the byproducts in the reaction of a terminal alkyne. 19 c Inspired by the above observations and our preliminary works, 19 which were facilitated by the readily available trifluoromethyl selenoxide as a trifluoromethylselenolation reagent, we developed in the current work a metal-free Lewis-acid-catalyzed divergent trifluoromethylselenolation of alkynes to construct α-trifluoromethylselenolated ketones and trifluoromethylselenolated alkynes (Scheme 1-3).…”
Section: Introductionmentioning
confidence: 99%